2018
DOI: 10.1007/s00256-018-2921-9
|View full text |Cite
|
Sign up to set email alerts
|

Normal imaging laterality on magnetic resonance imaging of the medial epicondyle of the elbow on the dominant side of adolescent male baseball players

Abstract: Larger ossification and cartilage size of the medial epicondyle in the dominant elbow suggested that the medial collateral ligament to the medial epicondyle induces excessive repetitive tensile stress, but without clinical symptoms. Functional or microanatomical damage of the medial epicondyle may induce a lower ossification signal in the dominant elbow, thereby decreasing fatty bone marrow and inducing sclerotic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similarly, other authors have assessed adaptive changes in the osseous structures of the elbow. Yoshizawa et al [13] demonstrated asymmetric enlargement of the medial epicondylar ossification center in the dominant compared to the nondominant elbow in 80 adolescent baseball players aged 9-14 years, suggesting that the UCL may induce excessive repetitive tensile stress on the medial epicondyle. Sada et al [14] showed an asymmetric increase in humerocapitellar volumetric bone mineral density and trabecular thickness in the dominant versus nondominant elbow of 17 baseball players aged 16-29 years, likely the result of repetitive valgus stresses generated by pitching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other authors have assessed adaptive changes in the osseous structures of the elbow. Yoshizawa et al [13] demonstrated asymmetric enlargement of the medial epicondylar ossification center in the dominant compared to the nondominant elbow in 80 adolescent baseball players aged 9-14 years, suggesting that the UCL may induce excessive repetitive tensile stress on the medial epicondyle. Sada et al [14] showed an asymmetric increase in humerocapitellar volumetric bone mineral density and trabecular thickness in the dominant versus nondominant elbow of 17 baseball players aged 16-29 years, likely the result of repetitive valgus stresses generated by pitching.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior bundle of the ulnar collateral ligament provides the main restraint against valgus stress at the elbow, making it particularly susceptible to injury in throwing athletes. A variety of anatomic adaptations can occur in response to repetitive valgus loading, including thickening of the ulnar collateral ligament (UCL) and osseous remodeling [9][10][11][12][13][14]. A spectrum of injuries can occur when these adaptive mechanisms fail as a consequence of compromised medial ligamentous integrity with resultant valgus instability resulting in accentuated loading of the radiocapitellar joint and excessive shear forces on the posteromedial elbow [6].…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 Changes to the medial epicondyle of the throwing side also have been identified from youth to adolescent baseball players through the use of ultrasonography, radiography, or MRI. 23 , 26 , 28 , 37 Therefore, it is possible that similar adaptive changes may exist in the elbows of throwing athletes caused by the effects of repetitive throwing on the ulnar sublime tubercle. As a result, our modified technique could be an efficient surgical option in patients who have a small medial epicondyle.…”
Section: Discussionmentioning
confidence: 99%